1996
DOI: 10.1073/pnas.93.21.11825
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled cholecystokinin-B/gastrin receptors are responsible for physiological cell growth of the stomach mucosa in vivo.

Abstract: Many peptide hormone and neurotransmitter receptors belonging to the seven membrane-spanning G protein-coupled receptor family have been shown to transmit ligand-dependent mitogenic signals in vitro. However, the physiological roles of the mitogenic activity through G protein-coupled receptors in vivo remain to be elucidated. Here we have generated G protein-coupled cholecystokinin (CCK)-B/ gastrin receptor deficient-mice by gene targeting. The homozygous mice showed a remarkable atrophy of the gastric mucosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
160
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(170 citation statements)
references
References 50 publications
8
160
2
Order By: Relevance
“…An amplified 155-bp DNA fragment underwent direct DNA sequencing for confirmation using Receptor binding study. To perform the in vitro gastrin binding experiment, we isolated the membrane fraction from GSM06 cells preincubated in the presence or absence of various peptides for 2 days at 33°C by homogenization and centrifugation at 42,000 g for 15 min as reported previously (27). The membrane fraction (1 mg) was labeled for 2 h at 24°C with 50 pM [ 125 I]gastrin in the presence of varying concentrations (10 ÏȘ11 to 10 ÏȘ6 M) of nonlabeled gastrin, CCK-8, or G-Gly.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…An amplified 155-bp DNA fragment underwent direct DNA sequencing for confirmation using Receptor binding study. To perform the in vitro gastrin binding experiment, we isolated the membrane fraction from GSM06 cells preincubated in the presence or absence of various peptides for 2 days at 33°C by homogenization and centrifugation at 42,000 g for 15 min as reported previously (27). The membrane fraction (1 mg) was labeled for 2 h at 24°C with 50 pM [ 125 I]gastrin in the presence of varying concentrations (10 ÏȘ11 to 10 ÏȘ6 M) of nonlabeled gastrin, CCK-8, or G-Gly.…”
Section: Animalsmentioning
confidence: 99%
“…CCKA-Rs exhibit a 500-to 1,000-fold higher affinity for sulfated analogs of CCK than for gastrin, whereas CCKB-Rs have approximately equal affinity for both sulfated and non-sulfated peptide analogs of CCK and gastrin (32,34,46,47). CCKB-Rs are present in parietal, ECL, and probably somatostatin cells (2,4,23,27,28,41 (2,28). Immunohistochemical studies have also demonstrated the distribution of CCKB-R in the same cell types (41).…”
mentioning
confidence: 99%
“…Mice that lack the gastrin gene or the gastrin/ cholecystokinin-B receptor have altered gastric mucosal architecture and differentiation (Nagata et al, 1996;Koh et al, 1997;Friis-Hansen et al, 1998). Gastrin and gastrin receptor-null mice exhibit reduced numbers of enterochromaffin-like cells and an expansion of mucous and surface epithelial cells (Nagata et al, 1996;Koh et al, 1997;Friis-Hansen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Gi-mediated GPCRs, were shown to produce a mitogenic response which was blocked by the tyrosine A recent study has shown, using gene knock-out studies, that certain GPCRs are essential for ce11 growth under physiologicd conditions (Nagata et al, 1996). Activation of GPCRs l a d s to rapid phosphorylation and activation of MAP kinases.…”
mentioning
confidence: 99%